Research on Beampattern Synthesis of Conformal Array Based on Space-Variability Suppression - Sijia Liu; Minghai Pan (Sensors)
In order to solve the problem that the array beampattern varies greatly with the angle during spatial scanning, this paper presents a synthesis method of the conformal array beampattern based on “spatial-variability (SV)” suppression. In order to obtain a stable beampattern, the convex optimization method is used to solve the weighted value of the amplitude and phase of the elements under the condition of satisfying the set beam gain threshold so that the optimized main lobes of the beams with different directions approach the main lobe of the reference beam. Since beams of different dimensions have different broadening degrees after optimization, we weighted the objective function and solved the optimal weights by the golden section search method (GSM) to improve the comprehensive optimization results of two-dimensional beams. The simulation results demonstrate the effectiveness of the proposed method.